Environmental transmission of Clostridioides difficile ribotype 027 at a long-term care facility; an outbreak investigation guided by whole genome sequencing. (26th September 2018) - Endres, Bradley T.; Dotson, Kierra M.; Poblete, Kelley; McPherson, Jacob; Lancaster, Chris; Bassères, Eugénie; Memariani, Ali; Arnold, Sandi; Tupy, Shawn; Carlsen, Conner; Morehead, Bonnie; Anyatonwu, Sophia; et al.
Abstract: Objective: This article describes a CDI outbreak in a long-term care (LTC) facility that used molecular typing techniques and whole-genome sequencing to identify widespread dissemination of the clonal strain in the environment which was successfully removed after terminal cleaning. Setting: This study was conducted in a long-term care facility in Texas. Methods: A recently hospitalized LTC patient was diagnosed with CDI followed shortly thereafter by 7 subsequent CDI cases. A stool specimen was obtained from each patient for culturing and typing. An environmental point-prevalence study of the facility was conducted before and after terminal cleaning of the facility to assess environmental contamination. Cultured isolates were typed using ribotyping, multilocus variant analysis, and whole-genome sequencing. Results: Stool samples were available for 5 of 8 patients; of these specimens, 4 grew toxigenic C. difficile ribotype 027. Of 50 environmental swab samples collected throughout the facility prior to the facility-wide terminal cleaning, 19 (38%) grew toxigenic C. difficile (most commonly ribotype 027, 79%). The terminal cleaning was effective at reducing C. difficile spores in the environment and at eradicating the ribotype 027 strain ( P <.001). Using multilocus variance analysis and whole-genome sequencing, clinical and environmental strains were highly related and, in some cases, were identical. Conclusion: Using molecular typing techniques, we demonstrated reduced environmental contamination with toxigenic C. difficile and the eradication of a ribotype 027 clone. These techniques may help direct infection control efforts and decrease the burden of CDI in the healthcare system.